snowBOTS: a mobile robot on snow covered ice - Fredriksson, Håkan; Rönnbäck, Sven; Berglund, Tomas; Wernersson, Åke; Hyyppä, Kalevi (Luleå tekniska universitet, EISLAB, 2007)
We introduce snowBOTs as a generic name for robots working in snow. This paper is a study on using scan ning range measuring lasers towards an autonomous snow cleaning robot, working in an environment consisting al most entirely of snow and ice. The problem addressed here is using lasers for detecting the edges generated by "the snow meeting the road". First the laser data were ﬁltered using his togram/median to discriminate against falling snowﬂakes and small objects. Then the road surface was extracted us ing the range weighted Hough/Radon transform. Finally the left and right edges of the road was detected by thresh olding. Tests have been made with a laser on top of a car driven in an automobile test range just south of the Arctic Circle. Moreover, in the campus area, the algorithms were tested in closed loop with the laser on board a robotized wheelchair. Validerad; 2007; 20070910 (hf) CASTT - Centre for Automotive Systems Technologies and Testing